Neonatal mpox in Nigeria: a case of transplacental or postnatal transmission - Chizaram Anselm Onyeaghala; Ezioma Anne Alinnor; Mary Irabor; Jennifer Ngufan Nongo; Idorenyin Diamond; Chioma Ada Nnah; Uju Stella Azubogu; Paul Ichendu Nsirimobu; Omosivie Maduka; Peace Opara; Rosemary Ogochukwu Ugwu; Datonye Dennis Alasia (BMC Infectious Diseases)
Abstract Background Little information exists in the literature regarding the burden and impact of mpox infection in the newborn population since the detection of the first case of human mpox over five decades ago. Case presentation We report a case of laboratory-confirmed mpox in a full-term male neonate with HIV-exposure who presented with a febrile vesiculo-pustular rash syndrome and a centrifugal pattern of distribution (marked on the scalp, face, neck and limbs and sparse on the thorax and abdomen) on day 16 of life at the University of Port Harcourt Teaching Hospital, Rivers State, Nigeria. He had his first skin eruption on the fourth day of life. There was a history of similar lesions in both parents, who are living with human immunodeficiency virus. Vesicular fluid polymerase chain reaction testing confirmed the presence of monkeypox virus (MPXV) DNA and was negative for varicella-zoster virus. Despite the diagnosis of mpox in the early neonatal period with the high likelihood of a transplacental route of transmission, the possibility of a postnatal transmission could not be entirely ruled out. He was optimized on supportive care including nutrition, skin care, fluid management, blood transfusion, and the use of targeted antibiotics. While on admission, he developed bacterial skin co-infection with methicillin-resistant Staphylococcus aureus, prolonged illness, and eventually recovered following a delayed time to resolution of skin lesion of 48 days. Conclusions Neonatal mpox infection is rare and could lead to prolonged morbidity and mortality. Clinicians should always maintain a high index of suspicion and consider mpox in the differential diagnosis of a neonatal vesiculo-pustular rash, particularly if there is a history of similar rash in the family, as early disease recognition and early treatment are associated with improved outcomes. Further studies are needed to better understand the transmission routes of MPXV in newborns.